Scattering From a Conducting Cylinder Partially Buried in A Dielectric Half Space by a Decomposition Method - Kizilay, Ahmet; Saynak, Ugur (IEEE, 2016)
A new method for solving scattering from a cylinder partially buried in a material half space for TMz polarization is presented with example scenarios. The surface equivalence principle is used with the decomposition method in order to calculate the current densities in the calculation domain. The Method of Moments (MoM) is used to solve the electric field integral equations (EFIE) in the frequency domain.
Keywords: Method of Moments; Scattering; Partially-buried; SOMMERFELD INTEGRALS; Engineering; Telecommunications